2023
DOI: 10.20945/2359-3997000000606
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological profile of congenital hypothyroidism at a southern Brazilian state

Abstract: Objective: To determine the incidence of congenital hypothyroidism (CH) over a 10-year period at the Reference Service in Neonatal Screening of the state of Rio Grande do Sul (RSNS-RS). Subjects and methods: Historical cohort study including all newborns screened for CH by the RSNS-RS from January 2008 until December 2017. Data of all newborns with neonatal TSH (neoTSH; heel prick test) values ≥ 9 mIU/L were collected. According to neoTSH values, the newborns were allocated into two groups: Group 1 (G1), compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
1
0
0
Order By: Relevance
“…Furthermore, the present study showed no significant relationship between the history of parental consanguinity and CH. Aligned with the results of our study, other studies in Iran and Brazil found no significant association between CH and parental consanguinity (24)(25)(26). This observation contradicts the findings of three studies in Iran, suggesting that parental consanguinity could be a probable cause of the high prevalence of CH (27)(28)(29).…”
Section: Discussionsupporting
confidence: 56%
“…Furthermore, the present study showed no significant relationship between the history of parental consanguinity and CH. Aligned with the results of our study, other studies in Iran and Brazil found no significant association between CH and parental consanguinity (24)(25)(26). This observation contradicts the findings of three studies in Iran, suggesting that parental consanguinity could be a probable cause of the high prevalence of CH (27)(28)(29).…”
Section: Discussionsupporting
confidence: 56%